Depiction of mental illness and psychiatry in popular video games over the last 20 years - Buday, Jozef; Neumann, Miroslav; Heidingerová, Jana; Michalec, Jirí; Podgorná, Gabriela; Mareš, Tadeáš; Pol, Marek; Mahrík, Jakub; Vranková, Stanislava; Kališová, Lucie; Anders, Martin (Frontiers in Psychiatry, 2022)
Video games represent a rapidly growing media form that is a daily activity for many youths. So far, only a little attention has been paid to the portrayal of mental illnesses and psychiatric intervention within them. In our research, we explored the best-selling video games released between 2002-2021 in order to analyse these representations. We came to the conclusion that approximately 1 out of 10 popular games attempts to portray symptoms of mental illness – with a majority of 75% of them in a negative and stereotypical way. Despite the majority of mental illness depiction in popular video games being negative, there are mounting reports that certain representations have a positive impact on their player bases. Further studies are required, as to how much videogames influence the player’s attitude towards this topic.